The Evaluation of short-term and long-term effects of fibrinolytic drug Alteplase on catheters dysfunction in dialysis patients: Effects of Alteplase on catheters dysfunction - Moradi, Yeganeh; Golmohammadi, Sima; Sobhieh, Mohammadreza; Kalbasi, Saeed; Futuhi, Farzaneh (Student Research in Translational Medicine, 2022)
Introduction: Despite the tendency to important infectious and mechanical complications, central venous catheters have become a common means of vascular access worldwide for patients requiring hemodialysis. In some studies, the use of fibrinolytic drugs is effective in the treatment of catheter function problems. In this study, the effects of Alteplase (a fibrinolytic drug) on catheter function was investigated. Methods: This study was performed on 100 dialysis patients in the dialysis ward of Imam Reza Hospital in Kermanshah (Iran) who had a catheter dysfunction. After confirmation by the nephrologist, in case of catheter dysfunction and failure to resolve it with the usual methods, one milligram of Alteplase with normal saline was added to each lumen of the catheter and left in place for one hour. After aspirating the lacquered solution, the rate of blood outflow was assessed by aspiration, and catheter function was evaluated. Results: The mean age was 60.31 +- 11.67 years. 52 patients were male and 48 patients were female. In terms of catheter implantation time, 20 patients were less than 3 months, 12 patients were between 3 to 6 months and 68 patients were more than 6 months. The duration of proper catheter function after injection was less than 3 months in 11 patients, between 3 to 6 months in 31 patients, and more than 6 months in 58 patients. Only 6 out of 100 cases received 2 mg and others received 1 mg of the drug. 25 patients had the insufficient effect of the drug on catheter function in terms of blood flow velocity, and in 75 patients this effect was good. Only 8 patients had inoperable lock catheters. Out of 100 patients studied, 7 had temporary catheters and 93 had permanent catheters. Conclusion: Alteplase is safe and effective on catheter function in hemodialysis patients.